Kajian Komparasi Kinerja Sludge Separator dan Dekanter 3 Fasa Pabrik Kelapa Sawit (PKS) - Arjanggi Nasution; M. Ansori Nasution; Meta Rivani; Henny Lydiasari; Ayu Wulandari (Jurnal Penelitian Kelapa Sawit, 2022)
The technology used to reduce oil loss at output sludge from underflow Continuous Settling Tank (CST) is a sludge separator and 3-phase decanter. In POM A, oil extraction is done manually with an oil loss rate of 0.36 tons/hour or 7.83 m3/day. The resulting oil loss figures indicate that extracting the oil using a sludge separator or 3-phase decanter is necessary. The research method used in this study is the comparison of primary data and secondary data on the working principle, the number of supporting equipment, electrical power requirements, operations, maintenance, investment costs, and waste quality. Primary data used oil content, flow rate, and temperature of CST underflow liquid; oil content and effluent flow rate from the final drab output; the amount of oil quoted and returned to the POM. Secondary data in the form of POM performance reports, waste production reports, and data on the specifications of the sludge separator and 3-phase decanter from producers. The working principle of the sludge separator and 3-phase decanter are particle size, bowl layout, bowl rotation direction, output type, sludge capacity, equipment capacity, and oil loss. The 3-phase decanter has 28 units of processing support equipment, more than the 22 units of sludge separator. The power requirement of the sludge separator is 45-60 kWh with a total of 3 units, and a 3-phase decanter requires an electrical power of 22-55 kWh with a capacity of 1 unit. Operationally there are supporting factors for sludge separator, including temperature, nozzle size, and bowl rotation, while supporting aspects for 3-phase decanter include flow rate and feed composition, centrifugal and differential speeds, depth of clarification zone, and weir liquid discharge opening. Maintenance of sludge separator and 3-phase decanter influenced by diluent water, operation, and damage factors. The range of investment costs in the procurement of sludge separators is IDR 0.863-1.837 billion, while the 3-phase decanter is IDR 3.804-5.825 billion. The quality of the 3-phase decanter waste is better than the sludge separator. These results indicate that the most effective tool for processing CST sludge output is a 3-phase decanter. Comparison of the working principle of 3-phase sludge separator and decanter.